Summary of Large-Scale Graph Partitioning Algorithms - Xu, Jinfeng; Dong, Yihong; Wang, Shiyi; He, Xianmang; Chen, Huahui (Dianxin Kexue, 2014)
The large-scale graph partitioning algorithms were summarized and graph computing models in the distributed environment were introduced. Firstly the large-scale static graph partitioning algorithms and the dynamic graph partitioning algorithms were discussed. Then the advantages and disadvantages of these algorithms and its adaptability conscientiously were sumed up. Finally, some meaningful research subjects about the distributed graph partition, which have not been explored were pointed out.